2022
DOI: 10.1155/2022/6481846
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-192-5p Alleviated Fibrosis and Inflammatory Responses of Tendon Cells by Targeting NFAT5

Abstract: Objective. To explore the effect of microRNA (miR)-192-5p on the inflammatory and fibrotic responses of tendon cells. Methods. Tendon cells were treated with transforming growth factor-β1 (TGF-β1). The expression of miR-192-5p and nuclear factor of activated T cells 5 (NFAT5) in tendon cells were detected by RT-qPCR. The expressions of inflammatory and fibrosis-related factors were detected by RT-qPCR and Western blot. MiR-192-5p binds to NFAT5 targeting by TargetScan and dual-luciferase reporter gene assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…From the target mRNAs literature data, which focalized on skeletal muscle metabolism and inflammatory pathways, we found PIM1 and ZEB2 for hsa-miR-192-5p, which are involved in skeletal muscle differentiation and regeneration, and LATS2 and VEGFA for hsa-miR-372-3p, which are involved in skeletal muscle growth and aging. We also included one predicted mRNA target (NFAT5) for has-mir-192-5p using recently available literature data not included in the last update of the software [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the target mRNAs literature data, which focalized on skeletal muscle metabolism and inflammatory pathways, we found PIM1 and ZEB2 for hsa-miR-192-5p, which are involved in skeletal muscle differentiation and regeneration, and LATS2 and VEGFA for hsa-miR-372-3p, which are involved in skeletal muscle growth and aging. We also included one predicted mRNA target (NFAT5) for has-mir-192-5p using recently available literature data not included in the last update of the software [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, hsa-miR-192-5p expression inhibits the NFAT5 regulation on fibrosis-related cytokines and inflammatory cytokine expression. At the same time, hsa-miR-192-5p reduces the TGF-β1-induced inflammatory response and apoptosis in tendon cells [ 26 ]. ZEB2, a predicted target for hsa-miR-192-5p, is expressed in murine skeletal muscle tissue and has an important role in the skeletal muscle differentiation of pluripotent stem cells and in muscle tissue regeneration from adult myogenic progenitors [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%